Eco-audit in e-learning implementation of FSKKP - Ng Kah, Yee (2013)
This project is to develop a Eco-Audit In E-Learning Implementation Of FSKKP. Eco-audit is an examination of activity of an organization affect the environment. To raise the awareness of online learning Moodle users on environmental issues, eco-audit is implementing into online learning system Moodle. Thus, the eco-audit is built with the function for paper pages measurement on their action during the use of Moodle. Main purpose for develop the Eco-audit tool is to increase the awareness and knowledge of eco-audit among students and lecturers through eLearning by using data visualisation. This eco-audit will be helping to beneficial the actions and activities of online users in online learning system which related to text deliver action such as quiz, assignment and file resources module. In a nutshell, user can review their detail of saving paper and realise their activities using Moodle is beneficial to environment.